An antibiotic‐resistant class 3 integron in an Enterobacter cloacae isolate from hospital effluent. (4th March 2013) - Barraud, O.; Casellas, M.; Dagot, C.; Ploy, M.‐C.; Cantón, R.
Abstract Hospital effluents are involved in dissemination of antibiotic‐resistant integrons. We describe here a new class 3 integron, In3‐5, detected in an Enterobacter cloacae isolate retrieved from a random French hospital effluent sample collected in 2009. In3‐5 carries two gene cassettes: the new blaOXA‐256 and an aac(6′)‐Ib variant, respectively conferring resistance to β‐lactams and aminoglycosides. In3‐5 is located on an IncQ‐like backbone plasmid. Class 3 integrons could thus be involved in the dissemination of antibiotic resistance in both clinical settings and the environment, and could participate in the exchange of antibiotic‐resistance genes between these two ecosystems.